Comparison of Differentially Expressed Genes in Human Versus in Chimeric Mouse Livers Following HBV Infection - Huarui Bao; Masataka Tsuge; Serami Murakami; Yasutoshi Fujii; Shinsuke Uchikawa; Hatsue Fujino; Atsushi Ono; Eisuke Murakami; Tomokazu Kawaoka; Daiki Miki; Clair Nelson Hayes; Shiro Oka (Livers, 2025)
Background/Objectives: Hepatitis B virus (HBV) infection is a worldwide health problem responsible for chronic liver disease and hepatocellular carcinoma. Both innate immunity and the adaptive immune response play central roles in the development of chronic hepatitis and liver cancer. We previously performed a comprehensive analysis of gene expression in the livers of HBV-infected chimeric mice and found that several genes associated with cell growth or carcinogenesis via hypoxia and KRAS signaling were upregulated by HBV infection. However, due to the absence of adaptive immunity in uPA/SCID chimeric mice, we were unable to analyze the effect of the host immune response. Methods: In this study, we compared gene expression profiles in the livers obtained from HBV-infected chimeric mice with those of HBV carriers. Results: After HBV infection, the expression of genes associated with inflammation and immune response, especially involving the Th1 and Th2 activation pathways, was altered as HBV-specific intracellular immune responses both in vivo and in clinical samples. Interestingly, the proinflammatory gene IL12A was induced by HBV infection in the chimeric mouse livers but not in the human livers, and associated genes, such as SRDA5A2, AR, and CCR3, showed differential alteration by HBV infection between the chimeric mouse and human livers. Conclusions: These results suggest that hepatocarcinogenesis may be suppressed by host immunity in HBV carriers. This study highlights potential new implications for inhibiting the progression of HBV-related liver diseases, including hepatocarcinogenesis.